A literature review of record linkage procedures focusing on infant health outcomes - Machado Carla Jorge (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
Record linkage is a powerful tool in assembling information from different data sources and has been used by a number of public health researchers. In this review, we provide an overview of the record linkage methodologies, focusing particularly on probabilistic record linkage. We then stress the purposes and research applications of linking records by focusing on studies of infant health outcomes based on large data sets, and provide a critical review of the studies in Brazil.